Finance director (Henry Stewart Talks, 2026)
Finance Director/CFO Role, Investment Appraisal & Decisions, Risk Management & Mitigation, Behavioural & Psychological Biases, Adapting to Market Changes & Leadership, Balancing Shareholders & Corporate Social Responsibility